2023
DOI: 10.1097/ju.0000000000003021
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Lower Urinary Tract Dysfunction in the First Year After Spinal Cord Injury: A Descriptive Study of Urodynamic Findings

Abstract: Purpose: We aimed to provide a real-world description of neurogenic lower urinary tract dysfunction within the first year after spinal cord injury with a focus on unfavorable urodynamic parameters that are associated with urological morbidity. Materials and Methods: Urodynamic investigations from 97 patients with traumatic or ischemic acute spinal cord injury and managed according to the European Association of Urology Guidelines on Neuro-Urology were analyzed at a single university spinal cord injury center a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…NDO associated with DSD was the most related unfavorable VUDS findings reported by Kozomara et al in up to 88% of 97 patients with traumatic or ischemic acute spinal cord injury in the first year after the incident. Early detection of the association between NDO and DSD allows for timely management of their potential complications [ 45 ]. Shin et al have demonstrated that follow-up UDS can not only confirm improvement in bladder storage volume and pressure but also that it has been correlated to a better-estimated plasma flow on nuclear renogram [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDO associated with DSD was the most related unfavorable VUDS findings reported by Kozomara et al in up to 88% of 97 patients with traumatic or ischemic acute spinal cord injury in the first year after the incident. Early detection of the association between NDO and DSD allows for timely management of their potential complications [ 45 ]. Shin et al have demonstrated that follow-up UDS can not only confirm improvement in bladder storage volume and pressure but also that it has been correlated to a better-estimated plasma flow on nuclear renogram [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…UDS is costly when taking into account the purchase of equipment and disposables, as well as the requirement for specialized staff. Early intervention based on urodynamic findings rather than initiating treatment only once complications of NLUTD are present could, however, spare resources and reduce overall costs [ 45 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While none of the other studies reported on the presence of VUR, in our cohort, fortunately, only one patient had a VUR (i.e., grade 1). While VUR can be a complication after a prolonged period of high intravesical pressure in individuals with NLUTD [ 33 ], recent studies reported a similar low prevalence of VUR in individuals with acute SCI (i.e., within the first year after injury) [ 27 , 34 ]. Given the paucity of longitudinal urodynamic data in patients with MCS/UWS, at the present time, one can only refer to other entities of NLUTD, such as SCI and MS, regarding the risk of developing VUR long-term.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after spinal cord injury (SCI, which occurs in 3–10/100,000 people), NLUTD is almost universal, with 90% of traumatic SCI patients having an unfavorable urodynamic finding in the 1 st year after their injury. [ 2 ] This is similar in spina bifida (SB, which occurs in approximately 30–40/100,000 people) where almost all people have some sort of bladder impairment, and over half have urinary incontinence. [ 3 ] Other diseases such as multiple sclerosis (MS, 80–250/100,000 depending on the country) tend to have increased NLUTD symptoms as the disease progresses.…”
Section: Introduction To Neurogenic Lower Urinary Tract Dysfunctionmentioning
confidence: 96%